THE RELATONSHIP BETWEEN THE INTAKE OF ENERGY,PROTEIN, VITAMIN A AND ZINC (Zn) AND STUNTING IN THE AGE OF EARLY PERIOD IN ENTERING SCHOOL IN CANDIREJO VILLAGE - Kumaladewi, Desy; Maryanto, Sugeng; Septiar Pontang, Galeh (UNIVERSITAS NGUDI WALUYO, 2015)
Stunting is one of the effects of lack of nutrients that lasts a long time. Stunting can occur due to deficiency of macronutrients and macronutrients that play a role in the growth, such as energy, protein, vitamin A and zinc (Zn). The aim of this study was determine the relationship between the intake of energy, protein, vitamin A and zinc (Zn) and the incidences of stunting in children of school age in Candirejo Village This research was The study correlation with cross sectional approach. The population in this study were all first year students in Candirejo village. It obtained 56 children with total sampling method. Method of data taking used microtoise, digital scale and FFQ. Bivariate analysis used Pearson product moment and alternative test of Spearman rho (Î±=0,05) The average energy intake in children was 86.5% RDA. The average protein intake in children was 106.3% RDA. The average intake of vitamin A in children was 111.9% RDA. The average intake of zinc in children was 64.4% RDA. From 56 childs 37,5% was stunting and 62,5% no stunting. There was no relationship between the intake of energy, protein and vitamin A with the incidences of stunting (p = 0.129, p = 0.139, p = 0.200), and there was a correlation between zinc intake with the incidences of stunting (p = 0.014) There was no relationship between the intake of energy, protein and vitamin A with the incidences of stunting in children of school-age in Candirejo village. There was a relationship between zinc intake with the incidences of stunting in school-age children in the Candirejo village.